Role of Big Data in the Accounting Profession - Xie, Hongmei (International Journal of Management and Education in Human Development, 2022)
This paper discusses the impact of Big Data in my work in an accounting firm in China With technology expanding in almost every industry today, the accounting sector also is going through some significant transformation by evolving through traditional methods.Hence, industry professionals need to keep up with cutting-edge technologies to stay ahead of their competitors in the financial sector. In order to do so, big accounting firms have already started adopting technologiessuch as Big Data, Robotics, and Artificial Intelligence (AI) into their business models. Out of all the trending topics out there, big data is impacting nearly every aspect of the accounting industry. It helps produce better data-driven audits, hence, creating a better experience for clients as well as auditors. In the tax process, it helps evaluate tax codes, reduce fraud, and monitor budget and tax expenses, thereby saving time, money, and stress for filers. Whereas, in the advisory sector, it helps identify and monitor questions and create better reports to improve business performance. Moreover, in finance, it helps design analytical models and build better financial reports. Therefore, it is one of the most useful technologies that accountants need to adopt in their process.